Conditional cash transfers : - Fiszbein, Ariel (The World Bank, 2009)
The report also considers the rationale for conditioning the transfers on the use of specific health and education services by program beneficiaries. Thus CCTs have increased the likelihood that households will take their children for preventive health checkups, but that has not always led to better child nutritional status; school enrollment rates have increased substantially among program beneficiaries, but there is little evidence of improvements in learning outcomes. These findings suggest that to maximize their potential effects on the accumulation of human capital, CCTs should be combined with other programs to improve the quality of the supply of health and education services, and should provide other supporting services.